Analysis of The Meaning of “Mehamat Man Kalimbubu, Metenget Ersenina, Metami Man Anak Beru” in the Tradition of Rakut Sitelu in the Karo Community - Rambe, Oktaviani Rahmatin; Manalu, Arafat; Sembiring, Kartika Patricia S; Lubis, Ilman Nafi’an; Muliana, Dina; Wuriyani, Elly Prihasti (JAMPARING: Jurnal Akuntansi Manajemen Pariwisata dan Pembelajaran Konseling, 2025)
Indonesia is a country that has a diversity of ethnic groups totaling 1,340. One of them is the Karo tribe who live around Deli Serdang Regency, Binjai City, Medan City, Stabat, Dairi Regency and Karo Regency. The Karo tribe has a kinship system concept called "rakut sitelu" which is one of the elements of "sangkep nggeluh". Within the rakut sitelu kinship system, there are terms familiar to the Karo people, namely "Mehamat Man Kalimbubu", "Metenget Ersenina", and "Metami Man Anak Beru". These three terms are still firmly held by the Karo people and are part of the rakut sitelu. This research aims to reveal the meaning of the three terms and how they are correlated with the rakut sitelu tradition. This research design uses qualitative methods with data collection techniques through interviews, observations, and documentation studies. This research contributes to enriching the study of Karo culture, especially the rakut sitelu tradition. The results of this study are expected to be a reference for future researchers who want to further study the rakut sitelu tradition in Karo society. The results of this study which the meaning of mehamat man kalimbubu is respect for kalimbubu, metenget ersenina is maintaining social harmony and metami man anak beru is pampering or loving.